Blood metal levels and related antioxidant enzyme activities in patients with ataxia telangiectasia - Stefania Squadrone; Paola Brizio; Cecilia Mancini; Elisa Pozzi; Simona Cavalieri; Maria Cesarina Abete; Alfredo Brusco (Neurobiology of Disease, 2015)
Transition metals are cofactors for a wide range of vital enzymes and are directly or indirectly involved in the response against reactive oxygen species (ROS), which can damage cellular components. Their altered homeostasis has been studied in neurodegenerative disorders such as Alzheimer's disease (AD), Parkinson's disease (PD) and amyotrophic lateral sclerosis (ALS), but no data are available on rarer conditions.We aimed at studying the role of essential trace elements in ataxia telangiectasia (A-T), a rare form of pediatric autosomal recessive cerebellar ataxia with altered antioxidant response. We found an increased level of copper (Cu, p = 0.0002) and a reduced level of zinc (Zn, p = 0.0002) in the blood of patients (n. 16) compared to controls, using inductively coupled plasma mass spectrometry (ICP-MS). Other trace elements involved in the oxidative stress response, such as manganese (Mn) and selenium (Se), were unaltered. Cu/Zn-dependent superoxide dismutase (SOD1) was shown to have a 30% reduction in gene expression and 40% reduction in enzyme activity upon analysis of lymphoblastoid cell lines of patients (Student's t-test, p = 0.0075). We also found a 30% reduction of Mn-SOD (SOD2; Student's t-test, p = 0.02), probably due to a feedback regulatory loop between the two enzymes. The expression of antioxidant enzymes, such as erythrocyte glutathione peroxidase (GPX1), and SOD2 was unaltered, whereas catalase (CAT) was increased in A-T cells, both at the mRNA level and in terms of enzyme activity (~25%). Enhanced CAT expression can be attributed to the high ROS status, which induces CAT transcription.These results suggest that alterations in essential trace elements and their related enzymes may play a role in the pathogenesis of A-T, although we cannot conclude if altered homeostasis is a direct effect of A-T mutated genes (ATM). Altered homeostasis of trace elements may be more prevalent in neurodegenerative diseases than previously thought, and it may represent both a biomarker and a generic therapeutic target for different disorders with the common theme of altered antioxidant enzyme responses associated with an unbalance of metals.